Reticular adhesions are a distinct class of cell-matrix adhesions that mediate attachment during mitosis. Issue 11 (November 2018) - Lock, John; Jones, Matthew; Askari, Janet; Gong, Xiaowei; Oddone, Anna; Olofsson, Helene; Göransson, Sara; Lakadamyali, Melike; Humphries, Martin; Strömblad, Staffan
Abstract Adhesion to the extracellular matrix persists during mitosis in most cell types. However, while classical adhesion complexes, such as focal adhesions, do and must disassemble to enable mitotic rounding, the mechanisms of residual mitotic cell–extracellular matrix adhesion remain undefined. Here, we identify 'reticular adhesions', a class of adhesion complex that is mediated by integrin αvβ5, formed during interphase, and preserved at cell–extracellular matrix attachment sites throughout cell division. Consistent with this role, integrin β5 depletion perturbs mitosis and disrupts spatial memory transmission between cell generations. Reticular adhesions are morphologically and dynamically distinct from classical focal adhesions. Mass spectrometry defines their unique composition, enriched in phosphatidylinositol-4, 5-bisphosphate (PtdIns(4, 5)P2 )-binding proteins but lacking virtually all consensus adhesome components. Indeed, reticular adhesions are promoted by PtdIns(4, 5)P2, and form independently of talin and F-actin. The distinct characteristics of reticular adhesions provide a solution to the problem of maintaining cell–extracellular matrix attachment during mitotic rounding and division. Lock et al. identify reticular adhesion complexes that maintain cell–extracellular-matrix attachments during cell division. Reticular adhesions transmit spatial memory between cell generations, mediated by αvβ5 integrin and PtdIns(4, 5)P2 .